Pengaruh Discount, Service Quality dan Customer Experience Terhadap Repurchase Intention Pada Pengguna Layanan Shopeefood (Pada Mahasiswa FEB Unisma Malang) - Suwandini, Amelian Nisa; Sunaryo, Hadi; Mustapita, Arini Fitria (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to analyze and explain the influence of discounts, service quality and customer experience on repurchase intention among shopeefood service users. The population of this study were students from the Faculty of Business Economics, Malang Islamic University, majoring in management, class of 2020. The sampling technique used purposive sampling with the Slovin formula and 82 respondents were obtained. The data analysis method in this research is quantitative data analysis using SPSS. The research results show that the discount variable has a significant effect on repurchase intention among shopeefood service users, the service quality variable has no significant effect on repurchase intention among shopeefood service users, and customer experience has a significant effect on repurchase intention among shopeefood service users. Keywords: Discount, Service Quality, Customer Experience and Repurchase Intention